Assessing the Risk of a Canine Rabies Incursion in Northern Australia - Hudson, Emily G.; Brookes, Victoria J.; Ward, Michael P. (Frontiers in Veterinary Science, 2017)
Rabies is a globally distributed virus that causes approximately 60,00 human deaths annually with >99% of cases caused by dog bites. Australia is currently canine-rabies free. However, the recent eastward spread of rabies in the Indonesian archipelago has increased the probability of rabies entry into northern Australian communities. In addition, many northern Australian communities have large populations of free-roaming dogs, capable of maintaining rabies should an incursion occur. A risk assessment of rabies entry and transmission into these communities is needed to target control and surveillance measures. Illegal transportation of rabies-infected dogs via boat landings is a high-risk entry pathway and was the focus of the current study. A quantitative, stochastic, risk assessment model was developed to evaluate the risk of rabies entry into north-west Cape York Peninsula, Australia and rabies introduction to resident dogs in one of the communities via transport of rabies-infected dogs on illegal Indonesian fishing boats. Parameter distributions were derived from expert-opinion, literature and analysis of field studies. The estimated median probability of rabies entry into north-west Cape York Peninsula and into Seisia from individual fishing boats was 1.9x10-4/boat and 8.7x10-6/boat, respectively. The estimated annual probability that at least one rabies-infected dog enters north-west Cape York Peninsula and into Seisia was 5.5 x10-3 and 3.5x10-4, respectively. The estimated median probability of rabies introduction into Seisia was 4.7x10-8/boat and the estimated annual probability that at least one rabies-infected dog causes rabies transmission in a resident Seisia dog was 8.3x10-5. Sensitivity analysis using the Sobol method highlighted some parameters as influential, including but not limited to the prevalence of rabies in Indonesia, the probability of a dog on board an Indonesian fishing boat and the probability of a Seisia dog being on the beach. Overall, the probabilities of rabies entry into north-west Cape York Peninsula and rabies introduction into Seisia are low. However, the potential devastating consequences of a rabies incursion in this region make this a non-negligible risk.